Recombinant human insulin‐like growth factor‐1 therapy for 6 months improves growth but not motor function in boys with Duchenne muscular dystrophy. Issue 5 (16th March 2020) - Rutter, Meilan M.; Wong, Brenda L.; Collins, James J.; Sawnani, Hemant; Taylor, Michael D.; Horn, Paul S.; Backeljauw, Philippe F.
Abstract: Introduction: Recombinant human insulin‐like growth factor‐1 (rhIGF‐1) is a growth factor and has anabolic effects on muscle. We investigated whether rhIGF‐1 therapy: 1) improves or preserves muscle function; and 2) improves growth in boys with Duchenne muscular dystrophy (DMD). Methods: In this study we compared prepubescent, ambulatory, glucocorticoid‐treated boys with DMD (n = 17) vs controls (glucocorticoid therapy only, n = 21) in a 6‐month‐long, prospective, randomized, controlled trial of subcutaneous rhIGF‐1 therapy. The primary outcome was 6‐minute walk distance (6MWD). Secondary outcomes included height velocity (HV), change in height standard deviation score (ΔHtSDS), motor function, cardiopulmonary function, body composition, insulin sensitivity, quality of life, and safety. Results: Change in 6MWD was similar between groups (rhIGF‐1 vs controls [mean ± SD]: 3.4 ± 32.4 vs −5.1 ± 50.2 meters, P = .53). Treated subjects grew more than controls (HV: 6.5 ± 1.7 vs 3.3 ± 1.3 cm/year, P < .0001; 6‐month ΔHtSDS: 0.25, P < .0001). Lean mass and insulin sensitivity increased in treated subjects. Discussion: In boys with DMD, 6 months of rhIGF‐1 therapy did not change motor function, but it improved linear growth.